1994
DOI: 10.1093/infdis/170.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation Of Quantification Methods For Plasma Human Immunodeficiency Virus Type 1 Rna

Abstract: Six procedures for quantifying plasma human immunodeficiency virus type 1 (HIV-1) RNA were evaluated by nine laboratories. The procedures differed in their sample volume and preparation of samples and methods of amplification and detection. Coded samples in a 10-fold dilution series of HIV-1-spiked plasma were correctly ranked by all six procedures. Subsequently, coded duplicate plasma samples from 16 HIV-1-infected patients were tested using a common set of standards. Several HIV-1 RNA procedures were suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(55 citation statements)
references
References 25 publications
5
48
0
2
Order By: Relevance
“…p24 antigenemia has already been reported by many other authors (Winters et al 1993, Lin et al 1994, van Karkhoven et al 1994, Coste et al 1996. These results clearly showed the higher sensivity of viral load determination in comparison with p24 antigen detection.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…p24 antigenemia has already been reported by many other authors (Winters et al 1993, Lin et al 1994, van Karkhoven et al 1994, Coste et al 1996. These results clearly showed the higher sensivity of viral load determination in comparison with p24 antigen detection.…”
Section: Discussionsupporting
confidence: 65%
“…Conversely, other authors previously reported an inverse correlation between CD4 counts and HIV-1 RNA level (Winters et al 1993, Lin et al 1994, van Karkhoven et al 1994, Coste et al 1996. ß-2 microglobulin did not provide additional prognostic information and was found to be a non-specific marker of immune activation (Mellors et al 1997).…”
Section: Discussionmentioning
confidence: 90%
“…Using the HIV-CheX or Genscreen kit with any other kit would be an ineffective combination. One notable issue here is the discordance between the results of two assays (6,8,14), which can be resolved if better kits are used. Hence, this kind of evaluation gains importance for determining a better choice of kits.…”
Section: Discussionmentioning
confidence: 99%
“…The reported data were evaluated with the respect to the ability of the participants to obtain VL testing results that reproduce the known concentrations of HIV-1 RNA present in each DTS PT panel member. The results reported from the participants were grouped and analyzed by type of VL assay to avoid possible variability of the results among different types of VL assays (12)(13)(14). These groups were formed by a minimum of six participants using the same assay in each PT testing cycle.…”
Section: Methodsmentioning
confidence: 99%